ON THE MODULAR SEQUENCE SPACES GENERATED BY THE CESÀRO MEAN - Sukhdev Singh; Toseef Ahmed Malik (Ural Mathematical Journal, 2024)
In this paper, the seminormed Cesàro difference sequence space \( \ell(\mathcal{F}_j, q, g, r, μ, Δ_{({s})}^{t}, \mathcal{C})\) is defined by using the generalized Orlicz function. Some algebraic and topological properties of the space \(\ell(\mathcal{F}_j, q, g, r, μ, Δ_{({s})}^{t}, \mathcal{C}) \) are investigated. Various inclusion relations for this sequence space are also studied.